The pangenome structure of human pathogen Mycobacterium kansasii - Sur, Saubashya (Acta Biologica Szegediensis, 2023)
The non-tuberculous Mycobacterium kansasii, is the causative agent of destructive pulmonary and extrapulmonary infections in immunocompromised persons. Incessant use of multiple antibiotics and lack of effective vaccines did little to combat M. kansasii mediated infections. Here, a bioinformatic analysis has been carried out using PanExplorer, to analyze the pangenome aimed at functional characterization of the bacterium, understanding it’s pathogenic lifestyle and recognize the factors shaping evolution and variations amongst strains. M. kansasii had a large core genome (60.2%), a small (11.9%) dispensable genome and 27.9% strain-specific genes. The core genome of M. kansasii had a high concentration of COGs (Cluster of orthologous genes) linked to energy production and conversion, amino acid transport and metabolism, nucleotide transport and metabolism, coenzyme transport and metabolism, and secondary me-tabolite biosynthesis, transport and metabolism. Interestingly, numerous genes within the core and dispensable genome were associated with pathogenesis and virulence. Noteworthy among them were type VII secretion, ESX, PP and PPE family proteins. Although, M. kansasii genomes revealed overall relatedness and conservation, genomic rearrangements caused variability within the strains. The information from this analysis could assist future microbial genomics research on M. kansasii, and further studies, e.g., concerning distinctive gene clusters, and evolution.